Pengaruh Customer Experience dan Promosi Penjualan terhadap Repurchase Intention : (Studi pada Konsumen Nivea Men di Kota Medan) (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study aims to analyze the influence of Customer Experience and sales promotions on repurchase intention of Nivea Men consumers in Medan City. The background of the study is based on the increasing competition in the men's skincare industry which demands effective marketing strategies to maintain consumer loyalty. The research method uses a quantitative approach with an associative research type. The research sample consisted of 96 respondents determined by purposive sampling technique. The results showed that Customer Experience has a positive and significant effect on repurchase intention, with the Sense indicator as the dominant factor. Sales promotions also proved to have a positive and significant effect, with promotion quality as the most influential indicator. Simultaneously, both variables have a significant effect on repurchase intention, with Exploratory Interest as the highest indicator, which confirms that positive experiences and quality promotions can encourage consumers to make repeat purchases while exploring other products from the same brand. The implications of this study emphasize the importance of strengthening the Relate dimension in Customer Experience, consistent promotion frequency at strategic moments, and product differentiation to strengthen consumer preferences.